STUDI KAWASAN ISLAM (Studi Kasus di Istana Maimun Kota Medan) - Nurul Zannah, Putri Esaskia Silalahi (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2021)
Abstract : The Deli Sultanate was a Malay Islamic sultanate which was founded in 1632 by Tuanku Panglima Gocah Pahlawan in an area called Tanah Deli (now Medan City and Deli Serdang Regency). Judging from its historical heritage, the Malay Sultanate in Sumatra had a very big influence in developing Islam. One of them is the establishment of a magnificent palace in the middle of the city of Medan, namely the Maimun Palace. This palace is proof of the study that Medan City became an Islamic area that stood under the government of the Islamic Sultanate. This study aims to reveal the facts in the field related to proving that the Maimun Palace is a historical relic of the government of the Islamic region. This research method uses descriptive qualitative, which is in the type of ethnographic study so that it can reveal the actual reality and can understand cultural phenomena that reflect knowledge and meaning systems that guide the life of cultural groups. This study reveals the relationship between the Maimun Palace was built with Islam. This finding further makes it clear that several relics were found with the pattern of an Islamic empire or sultanate. Keywords: Islam, Maimun Palace, Deli Sultanate Abstrak : Kesultanan Deli merupakan sebuah kesultanan Islam Melayu yang didirikan pada tahun 1632 oleh Tuanku Panglima Gocah Pahlawan di wilayah bernama Tanah Deli (kini Kota Medan dan Kabupaten Deli Serdang). Dilihat dari peninggalan sejarahnya, Kesultanan Melayu di tanah Sumatera ini memiliki pengaruh yang sangat besar dalam mengembangkan Islam. Salah satunya yaitu berdirinya istana megah ditengah Kota Medan yaitu Istana Maimun. Istana ini menjadi bukti studi bahwasanya Kota Medan menjadi kawasan Islam yang berdiri dibawah pemerintahan Kesultanan Islam. Penelitian ini bertujuan untuk mengungkap fakta - fakta dilapangan terkait dengan pembuktian bahwa Istana Maimun menjadi peninggalan sejarah pemerintahan kawasan Islam. Metode penelitian ini menggunakan deskriptif kualitatif, yang berjenis studi etnografi sehingga dapat mengungkap realitas yang sebenarnya dan dapat memahami fenomena budaya yang mencerminkan pengetahuan dan sistem makna yang membimbing kehidupan kelompok budaya. Penelitian ini mengungkapkan adanya hubungan Istana Maimun dibangun dengan Islam. Temuan ini semakinmemperjelas bahwa ditemukannya beberapa peninggalan - peninggalan yang bercorak kerajaan Islam atau kesultanan. Kata kunci : Islam, Istana Maimun, Kesultanan Deli